2017
DOI: 10.1177/0886260517724832
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Crime Scene Behavior in Korean Homicide

Abstract: The aim of the current study is to identify themes of crime scene behaviors in a sample of 487 Korean homicides and test whether these themes are linked to offender characteristics. A content analysis of police information was first conducted and then a multidimensional scale approach was used to identify themes in the homicide data. The exploratory thematic structure showed four factors that confirmed the instrumental/expressive themes as being useful in differentiating homicides: sex-arousal, cognitive, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…The instrumental–planned category from the present study could be correlated with the instrumental–cognitive and instrumental–sexual arousal themes identified in other studies. In these categories, victims are targeted and the crime scene actions indicate planning (e.g., removing incriminating and forensic evidence).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The instrumental–planned category from the present study could be correlated with the instrumental–cognitive and instrumental–sexual arousal themes identified in other studies. In these categories, victims are targeted and the crime scene actions indicate planning (e.g., removing incriminating and forensic evidence).…”
Section: Discussionsupporting
confidence: 67%
“…Finally, offenders from the expressive–unplanned class showed some similarities with the themes of “overkill” or “blood” identified in previous studies . These offenders found themselves in situations where the crime was triggered by a loss of control mainly owing to their mental illness and was directed toward an intimate partner or family member.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The mean age of our samples in the current study is compatible with around 37 years reported in the official Crime Statistics of South Korea (see Kang & Park, 2008;CS, 2017). This is older than offender ages reported for the North America (Sea & Beauregard, 2017;UNODC, 2016).…”
Section: Personality-focused Typologiesmentioning
confidence: 66%